Criminal Justice College Instructors' Experiences, Perceptions, and Teaching Strategies Related to Undergraduate Plagiarism - Bond, Mark William (2016)
The criminal justice program in a community college located in the southwestern United States had experienced an increase in student plagiarism. However, the current teaching practices of criminal justice instructors to prevent and manage the increased student plagiarism have not been effective. The purpose of this study was to explore criminal justice college instructors' experiences, perceptions, and teaching strategies related to undergraduate student plagiarism using Goleman's emotional intelligence theory and Daloz's mentoring theory. Employing a qualitative instrumental case study design, data were collected through semistructured interviews with 10 criminal justice college instructors. Member checking and reflective journaling ensured accuracy and credibility with initial findings from the interview data. The interview data were coded and analyzed using matrix and thematic analysis. Findings revealed 6 categories: professional development, instructor-student relationships, Turnitin reports, policy enforcement, instructor discretion, and mentoring students. To address the findings, a department plagiarism policy was proposed through a position paper to key stakeholders at the community college. The implementation of the department plagiarism policy has the possibility to create positive social change by promoting ethical writing standards and providing support for students' future academic success